Enhancing multimedia communication components in instructional consulting service online: Students’ perspective and perception - Abdul Razak, Abd Hadi; Ang, Ling Weay (Computer Science Journal, 2010)
Online consultation - one of the advancement of communication technology in consulting service is conducted electronically in various contexts such as online medical consultation, IT consulting and online financial service consultation. It enables participants communicate in synchronous and asynchronous way [1]. However, implementation of this technology in instructional consultation in higher education is not fully integrated. This may due to lack of investigation, analyzing and proper strategy planning on problem encountered by students and lecturer. This paper discuss about the limitations of typical instructional consultation and students’ perspective and perception on conducting consulting service online. The potential benefits of communication components for students in higher education are determined by investigate their perceptions and perspectives on implementation of communication technology for online instructional consultation. The limitations of typical instructional consultation that elicited from literature review are included in this quantitative research study in order to investigate precisely students’ response pertaining to instructional consulting service in higher education.Data was solicited from a sample of 130 students in College of Arts and Science (CAS), College of Business (COB) and College of Law, Government and International Studies (COLGIS) in Universiti Utara Malaysia (UUM) via simple random sampling method. Student’s response to five point Likert-type scale anchored by the terms Strongly Disagree (1) to Strongly Agree (5), Not Important (1) to Extremely Important (5) and Never (1) to Very Often (5).The finding of the research revealed that students were generally positive about potential of multimedia communication tools for traditional consultation system in higher education organization.